2012
DOI: 10.1080/13691058.2011.631220
|View full text |Cite
|
Sign up to set email alerts
|

The compassion of concealment: silence between older caregivers and dying patients in the AIDS era, northwest Tanzania

Abstract: In northwest Tanzania, where AIDS has been present for 25 years, AIDS-related illness is a trigger through which community members discuss personal experiences of loss and assess social relationships. The terminal phase of AIDS demands intimate social relations between patients and caretakers. In this final phase of illness, caretakers are scrutinised for their behaviour towards the patient. In the moral world in which caregiving takes place, the act of concealing is considered an intrinsic part of proper care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The kinship network is a resilient source of social capital for the majority of those affected. In a context where in-patient healthcare is limited and those infected and affected by HIV require not only physical care but also financial support and in-kind assistance, these and other results demonstrate the remarkable ability families have to adapt to and respond to the implications of HIV in rural South Africa and beyond (Baylies, 2002;Cross, 2001;Iwelunmor et al, 2006;Seeley et al, 2008;Smit, 2007). This is not a new finding and not the major contribution of the paper but has relevance because it provides us with evidence from a dark period and place where despite access to ART, HIV was still the most common cause of illness and death.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The kinship network is a resilient source of social capital for the majority of those affected. In a context where in-patient healthcare is limited and those infected and affected by HIV require not only physical care but also financial support and in-kind assistance, these and other results demonstrate the remarkable ability families have to adapt to and respond to the implications of HIV in rural South Africa and beyond (Baylies, 2002;Cross, 2001;Iwelunmor et al, 2006;Seeley et al, 2008;Smit, 2007). This is not a new finding and not the major contribution of the paper but has relevance because it provides us with evidence from a dark period and place where despite access to ART, HIV was still the most common cause of illness and death.…”
Section: Discussionmentioning
confidence: 88%
“…Much of this research is framed by questions about the resilience of family functioning and the ability to resist dissolution in the face of the potential impacts of HIV and AIDS in the era largely before wide-scale access to treatment. South African evidence on the impacts of HIV on family suggest that although families experience difficulties providing support and may even be a burden, families in general are an important source of support and care for people living with HIV (Cross, 2001;Hosegood, Preston-Whyte, et al, 2007;Iwelunmor, Airhihenbuwa, Okoror, Brown, & BeLue, 2006;Smit, 2007). Thus, enabling resilience among those directly affected (Smit, 2007).…”
mentioning
confidence: 99%
“…People perceive AIDS as a deadly disease and often make no distinction between HIV and AIDS. Having HIV and AIDS is associated with being sick and approaching death and often people are afraid to test while HIV-positive people see no reasons for disclosure from the anticipation of severe stigma [5,22,[24][25][26][27].…”
Section: Construction Of Hivmentioning
confidence: 99%
“…HIV testing and disclosure are influenced by cultural and social contexts and to a greater extent by the understandings of HIV and AIDS which are grounded in broader understandings of the long-term illness, death, and social danger [4,22]. From the beginning of the HIV epidemic, HIV was conceptualized as highly stigmatizing, incurable, fatal, contagious, a threat to the life of others, physically degenerative and disfiguring, and associated with a painful or anesthetic death [23].…”
Section: Construction Of Hivmentioning
confidence: 99%
“…The authors argue that one reason why caregivers do not receive social recognition is because they conceal how much care is needed in order to protect the identity and reputation of the person for whom they are caring. Similarly, De Klerk ( 2012 ) found that parents may conceal the fact that their children have HIV/AIDS in order to protect the dignity of the family. In his classic book The Cloak of Competence , Edgerton ( 1993 ) describes how people with an intellectual disability try to conceal their disability and how caregivers not only help them in dealing with daily life, but also assist them in concealing their condition.…”
Section: Discussionmentioning
confidence: 99%